The Influence of Ewom And Attitude on Purchase Intention on Halal Cosmetics - Rima Fiandari, Yulist; Andarini, Sri Nastiti; Suryani, Wan (Bulletin of Management and Business, 2025)
The growing demand for halal cosmetics reflects increasing consumer awareness of religious compliance, health, and ethical concerns. This study aims to investigate the influence of Electronic Word of Mouth (EWOM) and consumer attitude on purchase intention toward halal cosmetic products in Indonesia. Using a quantitative approach, data were collected through an online survey from 160 female respondents aged 17 and above who are users of halal cosmetics. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) to examine the relationships among the variables. The findings reveal that EWOM has a significant positive influence on both attitude and purchase intention. Furthermore, attitude is found to have a strong and positive effect on purchase intention. These results confirm that EWOM not only shapes consumer evaluations but also directly drives behavioral intention. The study contributes to the halal consumer behavior literature by highlighting the psychological pathways through which EWOM influences purchasing behavior. Practically, the findings suggest that halal cosmetic brands should prioritize managing online consumer reviews and enhancing brand communication strategies to foster positive attitudes and encourage purchasing decisions.